Effects of Payroll Tax Cuts for Young Workers - Per Skedinger (Research Institute of Industrial Economics (IFN), 2014)
In response to high and enduring youth unemployment, large payroll tax cuts for young workers were implemented in two Swedish reforms in 2007 and 2009. This paper analyses the effects of the reforms on worker outcomes and firm performance in the retail industry, an important employer of young workers. In general, the estimated effects on job accessions, separations, hours and wages, are small. For workers close to the minimum wage the estimates suggest larger, but still modest, effects on the probability of job accession. There is also some evidence on increasing profits in a subsample of firms that employed relatively many young workers before the first reform, with estimated effects commensurate with small behavioural effects of the payroll tax cuts. The conclusion is that reducing payroll taxes is a costly means of improving employment prospects for the young.
Keywords: H21; H25; H32; J38; 330; Tax subsidy; Labour costs; Minimum wages; Retail industry